地面振动试验以及重量和平衡测量的系统和方法 (2017)
种用于提升飞行器（10）的设备可包含被安装在支撑表面（64）上的多个起重机构（74）。每个起重机构（74）可被配置为在飞行器（10）的组件（38）上给予个向上的力（90）其用于提升飞行器（10）脱离支撑表面（64）。该设备（70）包含被配置为安装到起重机构（74）的梁结构（100）。该设备（70）可还包含从梁结构（100）悬吊的起重横梁（140）。测量装置（178）可被安装到起重横梁（140）并且可被配置为啮合与组件（38）相关联的起重支点（54）以确定当飞行器被提升脱离支撑表面（64）时飞行器（10）的重量。 An apparatus for lifting an aircraft (10) may include a plurality of lifting mechanisms (74) mounted on a supporting surface (64). Each lifting mechanism (74) may be configured to impart an upward force (90) on a component (38) of the aircraft (10) for lifting the aircraft (10) off the supporting surface (64). The apparatus (10) may include a beam structure (100) configured to be mounted to the lifting mechanisms (74). The apparatus (10) may also include a lifting beam (140) suspended from the beam structure (100). A measurement device (178) may be mounted to the lifting beam (140) and may be configured to engage a jack point (54) associated with the component (38) to determine a weight of the aircraft (10) when the aircraft is lifted off the supporting s